2013
DOI: 10.1371/journal.pone.0063623
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Antiretroviral-Associated Lipodystrophy: Lipoatrophy, but Not Central Fat Gain, Is an Antiretroviral Adverse Drug Reaction

Abstract: BackgroundLipoatrophy and/or central fat gain are observed frequently in patients on antiretroviral therapy (ART). Both are assumed to be antiretroviral adverse drug reactions.MethodsWe conducted a systematic review to determine whether fat loss or gain was more common in HIV-infected patients on ART than in uninfected controls; was associated with specific antiretrovirals; and would reverse after switching antiretrovirals.ResultsTwenty-seven studies met our inclusion criteria. One cohort study reported more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 38 publications
5
69
0
Order By: Relevance
“…In South Africa, evidence suggests a decline in the use of over the counter cigarettes probably due to increased taxation, but there is a shift towards the use of ‘roll your own’ cigarettes particularly in rural areas [61]. A lower BMI in treatment naïve HIV infected people, is likely due to disease associated cachexia [62], while a lower BMI in those on treatment may result from lipoatrophy caused by antiretroviral medication [63]. …”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, evidence suggests a decline in the use of over the counter cigarettes probably due to increased taxation, but there is a shift towards the use of ‘roll your own’ cigarettes particularly in rural areas [61]. A lower BMI in treatment naïve HIV infected people, is likely due to disease associated cachexia [62], while a lower BMI in those on treatment may result from lipoatrophy caused by antiretroviral medication [63]. …”
Section: Discussionmentioning
confidence: 99%
“…Our data from both ANOVA and multiple regression analysis demonstrate a negative relationship of ART with both total body fat and BMC. In a recent systematic review of the lipodystrophic effects of ART it was shown that the use of antiretroviral agents is associated with lipoatrophy, and thus lower BMI [47]. Studies have also shown that ART is associated with reduced bone mass [48].…”
Section: Education Art and Snuff And Body Compositionmentioning
confidence: 99%
“…Furthermore, efavirenz's low genetic barrier to resistance requires high-level adherence to therapy for efficacy (Delaugerre et al, 2001;Riddler et al, 2008). HIV-infected patients receiving efavirenz also suffer from side effects such as depression, insomnia, skin rash, lipodystrophy, and lipoatrophy (Riddler et al, 2008;de Waal et al, 2013). On the other hand, rilpivirine prescription requires a heightened vigilance in clinical practice due to its unfavorable interaction with acid suppressant medication (Janssen et al, 2005;Rathbun and Liedtke, 2011).…”
Section: Introductionmentioning
confidence: 99%